2020
DOI: 10.1016/j.heliyon.2020.e03835
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evolution of the capsid (VP1) region in human norovirus genogroup II genotype 3

Abstract: Norovirus GII.3 has been suggested to be a prevalent genotype in patients with acute gastroenteritis. However, the genetic properties of the VP1 region encoding the major GII.3 antigen remain unclear. Here, we performed molecular evolutionary analyses of the GII.3 VP1 region detected in various countries. We performed time-scaled phylogenetic analyses, selective pressure analyses, phylogenetic distance analyses, and conformational epitope analyses. The time-scaled phylogenetic tree showed that an ancestor of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 55 publications
3
10
1
Order By: Relevance
“…A previous report showed that densely sampled short RdRp sequences provided more reliable evolutionary data than fewer longer sequences [ 26 ]. In the present study, the VP1 genes of the GII.3 showed a lower mean substitution rate (4.132 × 10 –3 substitutions per site per year) than in a previous report (4.82 × 10 –3 substitutions per site per year) [ 21 ]. Several factors, such as sequence numbers, methodology, and collection dates, may affect the differences in the evolutionary rates between the previous and present data.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…A previous report showed that densely sampled short RdRp sequences provided more reliable evolutionary data than fewer longer sequences [ 26 ]. In the present study, the VP1 genes of the GII.3 showed a lower mean substitution rate (4.132 × 10 –3 substitutions per site per year) than in a previous report (4.82 × 10 –3 substitutions per site per year) [ 21 ]. Several factors, such as sequence numbers, methodology, and collection dates, may affect the differences in the evolutionary rates between the previous and present data.…”
Section: Discussioncontrasting
confidence: 77%
“…The GII.3 [P21] strains evolved into two subclades and the corresponding GII.3[P12] formed two subclades in the evolution. Previous studies also showed that GII.3 VP1 sequences could be grouped into three major clusters, in which clusters II and III were compatible with the present SC I and SC II [ 21 ]. As both SC I and SC II contained the strains isolated in late 2010, it was likely that acquisition of a different RdRp gene allowed simultaneous evolution along with two distinct subclades.…”
Section: Discussionsupporting
confidence: 76%
“…Non-GII.4 genotypes, peak and ebb in prevalence [113,123,140]. GII.3, GII.6, GII.2, GII.12 and GII.17 are frequently detected [123,[141][142][143]. GI.3 is the most frequently detected GI genotype [122,123].…”
Section: Virus Backgroundmentioning
confidence: 99%
“…Two years later, these relatively larger clusters were further defined into five smaller lineages (A to E), which were generally observed to be temporally sequential in terms of collection dates of the corresponding strains within each lineage [22]. In 2020, Saito et al performed a phylogenetic analysis of a large number of sequences of GII.3 strains, most of which were collected after 2013, and therefore updated GII.3 classification with the analyzed strains being divided into three clusters (1, 2, and 3) based on the VP1 amino acid sequence [33].…”
Section: Introductionmentioning
confidence: 99%
“…Immunization of animals with GII.3 VLPs elicited antibodies capable of blocking the interaction between HBGAs and homotypic VLPs [34,37], indicating that the GII.3 VP1 protein does contain blockade antibody epitopes. Although in silico analyses have predicted several sites where GII.3 blockade antibody epitopes might reside [21,22,33], thus far, the exact locations of GII.3 blockade antibody epitopes have not been defined experimentally.…”
Section: Introductionmentioning
confidence: 99%